Inborn Error of Cobalamin Metabolism Associated with the Intracellular Accumulation of Transcobalamin‐Bound Cobalamin and Mutations in ZNF143, Which Codes for a Transcriptional Activator. Issue 9 (12th July 2016) - Pupavac, Mihaela; Watkins, David; Petrella, Francis; Fahiminiya, Somayyeh; Janer, Alexandre; Cheung, Warren; Gingras, Anne‐Claude; Pastinen, Tomi; Muenzer, Joseph; Majewski, Jacek; Shoubridge, Eric A.; Rosenblatt, David S.
Abstract : Mutations in a DNA regulating gene, ZNF143, cause a previously undescribed inherited disorder of vitamin B12 (cobalamin) metabolism. These mutations cause an accumulation of transcobalamin‐bound cobalamin within the cells, as well as decreased expression of MMACHC, a cobalamin trafficking protein. ABSTRACT: Vitamin B12 (cobalamin, Cbl) cofactors adenosylcobalamin (AdoCbl) and methylcobalamin (MeCbl) are required for the activity of the enzymes methylmalonyl‐CoA mutase (MCM) and methionine synthase (MS). Inborn errors of Cbl metabolism are rare Mendelian disorders associated with hematological and neurological manifestations, and elevations of methylmalonic acid and/or homocysteine in the blood and urine. We describe a patient whose fibroblasts had decreased functional activity of MCM and MS and decreased synthesis of AdoCbl and MeCbl (3.4% and 1.0% of cellular Cbl, respectively). The defect in cultured patient fibroblasts complemented those from all known complementation groups. Patient cells accumulated transcobalamin‐bound–Cbl, a complex which usually dissociates in the lysosome to release free Cbl. Whole‐exome sequencing identified putative disease‐causing variants c.851T>G (p.L284*) and c.1019C>T (p.T340I) in transcription factor ZNF143 . Proximity biotinylation analysis confirmed the interaction between ZNF143 and HCFC1, a protein that regulates expression of the Cbl trafficking enzyme MMACHC. qRT‐PCR analysis revealed low MMACHC expression levels both in patient fibroblasts, and in control fibroblasts incubated with ZNF143 siRNA.